Associations of egg consumption with cardiovascular disease in a cohort study of 0.5 million Chinese adults. Issue 21 (21st May 2018) - Qin, Chenxi; Lv, Jun; Guo, Yu; Bian, Zheng; Si, Jiahui; Yang, Ling; Chen, Yiping; Zhou, Yonglin; Zhang, Hao; Liu, Jianjun; Chen, Junshi; Chen, Zhengming; et al.
Abstract : Objective: To examine the associations between egg consumption and cardiovascular disease (CVD), ischaemic heart disease (IHD), major coronary events (MCE), haemorrhagic stroke as well as ischaemic stroke. Methods: During 2004–2008, over 0.5 million adults aged 30–79 years were recruited from 10 diverse survey sites in China. Participants were asked about the frequency of egg consumption and were followed up via linkages to multiple registries and active investigation. Among 461 213 participants free of prior cancer, CVD and diabetes, a total of 83 977 CVD incident cases and 9985 CVD deaths were documented, as well as 5103 MCE. Stratified Cox regression was performed to yield adjusted hazard ratios for CVD endpoints associated with egg consumption. Results: At baseline, 13.1% of participants reported daily consumption (usual amount 0.76 egg/day) and 9.1% reported never or very rare consumption (usual amount 0.29 egg/day). Compared with non-consumers, daily egg consumption was associated with lower risk of CVD (HR 0.89, 95% CI 0.87 to 0.92). Corresponding multivariate-adjusted HRs (95% CI) for IHD, MCE, haemorrhagic stroke and ischaemic stroke were 0.88 (0.84 to 0.93), 0.86 (0.76 to 0.97), 0.74 (0.67 to 0.82) and 0.90 (0.85 to 0.95), respectively. There were significant dose-response relationships of egg consumption with morbidity of all CVD endpoints (P for linear trend <0.05). Daily consumers also had an 18% lower risk of CVD death and a 28% lower risk of haemorrhagic stroke death compared to non-consumers. Conclusion: Among Chinese adults, a moderate level of egg consumption (up to <1 egg/day) was significantly associated with lower risk of CVD, largely independent of other risk factors.